Action Maze and Role Playing in comparison: A Randomized Field Trial on simulation-based teaching methodologies in critical care - Colacci, Teresa; Bonavoglia, Francesca; Dibattista, Francesca; Gargaro, Vincenza; Taborri, Sofia; La Torre, Giuseppe (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The training of healthcare professionals requires continuous innovation in teaching methodologies to foster the development of professional skills. The use of simulation in critical care is a proven effective technique, allowing students to acquire and consolidate the necessary knowledge to plan and implement nursing care in clinical practice. Interactive teaching strategies aim to increase student engagement and motivation in order to improve the learning process, decision-making, and critical thinking. New technologies that leverage gamification provide further advancements in interactive learning and represent a valuable and promising tool for training in various healthcare contexts. This study aims to analyze and compare two simulated teaching methodologies, Role Playing and Action Maze, and assess their effectiveness in terms of the acquisition of specific knowledge in the critical care field and the level of satisfaction among nursing students. Materials and Methods. A Randomized Field Trial was conducted. A total of 130 third-year nursing students from the Sapienza University of Rome were enrolled in the study, with 60 students from course D and 70 students from course X. An initial lecture was given on nursing care for critical patients. At the end of the lecture, a custom-designed questionnaire was administered to evaluate the knowledge acquired. The students were then randomly allocated into two groups: one group was assigned to Role Playing, and the other to Action Maze. At the end of the two simulated teaching activities, the questionnaire was administered again to assess changing in knowledge. Additionally, two validated scales, the Educational Practice Questionnaire Student Version and the Simulation Design Scale Student Version, were administered to assess student satisfaction and perception regarding the simulation techniques performed. Results. The Wilcoxon signed-rank test with Z=-2.1 and p=0.03, performed on the correct post-intervention responses, was significant with a p-value of <0.05 for the Action Maze group compared to the Role Playing group. The Simulation Design Scale Student Version scale showed a p-value of <0.05 for both the “teaching methodology” and “importance of elements” sections. The Educational Practice Questionnaire Student Version scale showed a p-value of 0.076 for the evaluation of the “importance of elements” section. Conclusions. The results of the study indicated that the Action Maze simulation teaching methodology was more effective, both in terms of knowledge acquisition and student satisfaction, compared to the Role Playing methodology. Further comparative studies are recommended to evaluate the effectiveness of the Action Maze compared to other simulated teaching methods.